Simulation And Experimental Studies Of Intake And Exhaust Tuning For Automotive Engine Low-End Torque Enhancement - Khoo, Aik Soon (2014)

(untitled)
Modern passenger car engines have been “down-sized” for improved fuel consumption, resulting in high speeds to obtain good performance. Consumers, however, are demanding improved low-end torque for improved drivability. The target engine; a 4 valve per cylinder, 1.6L engine with two intake cam profiles and 2 intake runner lengths, was modeled and correlated with measured engine performance characteristics (power, torque, etc.); and pressure traces from combustion chamber, intake and exhaust manifolds to establish the confidence level in the model's prediction. The model was then optimised for low-end torque by manipulating exhaust manifold configuration, exhaust runner length, intake diameter and intake runner length. It was found that the original exhaust system is too short and gives uneven exhaust cross-charging among the cylinders. Simulation result indicated that a 2.7-5.6% improvement in torque could be realised with an evenly cross-charged and longer exhaust runner. A 2% torque improvement was predicted by changing the intake manifold geometry to smaller diameter. The target engine was subsequently modified with new set of exhaust manifold and intake runner. Result showed a torque improvement of 2.7-4.5% at lower engine speed over the base design by exhaust tuning. Effect of intake tuning was not significant but it showed a similar trend as indicated by simulation.